Circulating tumor DNA detection in peripheral blood in postoperative efficacy evaluation and recurrence risk prediction of lung cancer - Lv, Kun; Yang, Xiongtiao; Li, Zhihua; Ma, Chengfang; Hong, Qiongchuan (Cellular and Molecular Biology, 2022)
This study mainly explores the application in the evaluation of postoperative efficacy and recurrence risk prediction. In this study, 50 lung cancer patients treated with thoracic surgery were selected. Collect the peripheral blood of these patients before the operation, separate the blood sample from the plasma by high-speed centrifugal separation, extract the DNA in the plasma by the magnetic bead method, and then extract the ctDNA. A liquid-phase chip capture system is used to highly concentrate target DNA. We use the IlluminaHiseq platform to sort with high throughput and high depth. As an indicator of ctDNA detection and analysis, the AF value of gene mutation frequency is used for calibration. The sensitivity of CEA detection in peripheral blood of tumor patients (TP) is 30% (15/50), and the sensitivity of ctDNA detection is significantly higher than that of CEA detection. Research results show that the number